Change we can believe in? the role and implications of culture and environmental values on climate change perceptions. - Heeren, Alexander (My University, 2012)
Climate change poses many ecological and social challenges to natural resource agencies. One great challenge that resource managers face is how to manage, or adapt, to climate change in a socially acceptable way. To meet this challenge, it is necessary to understand how public perceptions about climate change are formed and whether the public will support climate change management strategies. This issue was examined at the regional level (northeast Minnesota) using a conceptual framework tested with the results of focus groups and a mail survey. Chapter 1 of this thesis provides an introduction to the framework. The second chapter discusses the results of the focus groups examining how individuals talk about climate change. Chapter 3 tests the conceptual framework quantitatively using the results of a region wide mail survey. Finally, Chapter 4 provides a summary of the project and discusses directions that future research can take.
University of Minnesota M.S. thesis. August 2012. Major: Natural Resources Science and Management. Advisor:David C. Fulton. 1 computer file (PDF); vii, 117 pages, appendices p. 97-117.
Keywords: Adaptation; Climate change; Focus groups; Mail survey; northeast Minnesota; Public perceptions